Teach For America, Relay Graduate School, and charter school networks: The making of a parallel education structure - Angus Shiva Mungal (Arizona State University, 2016)
In New York City, a partnership between Teach For America (TFA), the New York City Department of Education (NYCDOE), the Relay Graduate School of Education (Relay), and three charter school networks produced a parallel education structure within the public school system. Driving the partnership and the parallel education structure are the free market ideologies that emerged in the late 1970s that helped to open education to outside organizations. This paper captures two intertwined phenomena; the formation of the parallel education structure and the various partnerships that helped built it. This has resulted in two unique pathways within the public school system. One pathway focuses upon local area conventional public schools that are administered by the NYCDOE. The other pathway represents failing local area public schools that are run by charter school networks. This paper looks beyond TFA's current influence within the classroom and explores how market forces led to its role with other educational organizations.